Resolving Domination Number pada Keluarga Graf Buku - Quthrotul Aini Fuidah; Dafik Dafik; Ermita Rizki Albirri (jcgant, 2020)
All graph in this paper are members of family of book graph. Let G is a connnected graph, and let W = {w_1,w_2,...,w_i} a set of vertices which is dominating the other vertices which are not element of W, and the elements of W has a different representations, so W is called resolving dominating set. The minimum cardinality of resolving dominating set is called resolving domination number, denoted by γ_r(G). In this paper we obtain the exact values of resolving dominating for family of book graph.